Energy expenditure, nutritional status, body composition and physical fitness of Royal Marines during a 6-month operational deployment in Afghanistan. Issue 5 (14th September 2014) - Fallowfield, Joanne L.; Delves, Simon K.; Hill, Neil E.; Cobley, Rosalyn; Brown, Pieter; Lanham-New, Susan A.; Frost, Gary; Brett, Stephen J.; Murphy, Kevin G.; Montain, Scott J.; Nicholson, Christopher; Stacey, Michael; et al.
<x content-type="archive" xml:space="preserve">Abstract</x> Understanding the nutritional demands on serving military personnel is critical to inform training schedules and dietary provision. Troops deployed to Afghanistan face austere living and working environments. Observations from the military and those reported in the British and US media indicated possible physical degradation of personnel deployed to Afghanistan. Therefore, the present study aimed to investigate the changes in body composition and nutritional status of military personnel deployed to Afghanistan and how these were related to physical fitness. In a cohort of British Royal Marines (n 249) deployed to Afghanistan for 6 months, body size and body composition were estimated from body mass, height, girth and skinfold measurements. Energy intake (EI) was estimated from food diaries and energy expenditure measured using the doubly labelled water method in a representative subgroup. Strength and aerobic fitness were assessed. The mean body mass of volunteers decreased over the first half of the deployment ( − 4·6 (sd 3·7) %), predominately reflecting fat loss. Body mass partially recovered (mean +2·2 (sd 2·9) %) between the mid- and post-deployment periods (P< 0·05). Daily EI (mean 10 590 (sd 3339) kJ) was significantly lower than the estimated daily energy expenditure (mean 15 167 (sd 1883) kJ) measured in a subgroup of volunteers. However, despite the body mass loss, aerobic fitness and strength were well maintained. Nutritional provision for British military personnel in Afghanistan appeared sufficient to maintain physical capability and micronutrient status, but providing appropriate nutrition in harsh operational environments must remain a priority.